Security and Performance-Based Design and Evaluation Criteria for Cryptographic Random Number Generators - Garıpcan, Ali Murat; Erdem, Ebubekir (My University, 2025)
This study comprehensively examines security and performance-oriented selection and evaluation criteria for Random Number Generators (RNGs) used in cryptographic applications. The study analyzes the fundamental differences between Pseudo Random Number Generators (PRNGs) and True Random Number Generators (TRNGs). Within the scope of these analyses, entropy sources, statistical characteristics, and performance metrics, as well as their effects on security, are evaluated. The ability of TRNGs to meet high security requirements thanks to their hardware-dependent structures is compared with PRNGs, which offer software-based and low-cost solutions. The study evaluates various criteria ranging from minimum entropy tests to space and energy requirements. It also highlights the fundamental challenges encountered in the design and implementation of RNGs in cryptographic systems. Additionally, the fundamental security requirements encountered in RNG design and how these requirements can be met in practice are discussed in detail. In this context, PRNGs, TRNGs based on physical processes, and hybrid RNG designs are analyzed. The advantages and disadvantages of these different design paradigms are then presented in a comparative manner. In conclusion, this study delivers a framework that unifies security, performance, and design considerations for RNGs, setting a benchmark for future cryptographic research. As a result, this framework forms the foundation for the next generation of secure, efficient, and scalable cryptographic systems.
Keywords: Entropy; Cryptography; Information security; Random number generators; Randomness